Leonid Andreyev’s Panpsychic Drama “Requiem” - H. Végh, Katalin (Slavica, 2026)
This article examines the role of Leonid Andreyev’s work in the emergence of the New Drama in Russia and, through an analysis of the play Requiem, highlights the genre-specific and formal characteristics of panpsychic dramas. The author emphasises that Andreyev’s panpsychic drama is a groundbreaking experiment that demonstrates just how far the concept of the dramatic genre can be expanded. The text of the panpsychic drama shows that eventfulness, previously considered one of the main criteria of drama, is by no means fundamental in the New Drama. In this way, the frequency of external events decreases, while the significance of internal events increases, and the role of mental and psychological events becomes increasingly important. On the other hand, Andreyev’s dramatic text already contains within itself an impoverishment of the referential function of artistic language, and the pursuit of the autonomy of tropes becomes the organizing principle of the drama’s structure. These phenomena give Andreyev’s drama panpsyche special significance on the way to the contemporary understanding of the New Drama.